Programming Windows Services with Microsoft Visual Basic 2008 - Gernaey, Michael (Microsoft Press, 2008)
Get the practical reference to developing Windows services with Visual Basic 2008. Addressing the leading trend of software as a service, this guide illustrates how developers with intermediate Visual Basic skills can design and implement Web services. It addresses a critical gap in the developer literature today, showing that services can be developed with Visual Basic 2008 and are not restricted to XML-based applications or Microsoft Visual C#. Software as a service is changing the dynamic between rich and thin clients. As device types multiply, users expect always-on connectivity to link them to the robust Web and corporate applications they use on the desktop. Services, which offload data storage and processing tasks to a server, run efficiently on Web platforms on any device. Services do not need to be a complex coding task and this is the ideal resource for creating modern, service-oriented applications. It covers integration of services with other Microsoft technologies, including Microsoft BizTalk Server, Microsoft Internet Information Services (IIS), and Microsoft SQL ServerTM. Plus, you ll get extensive code snippets and sample applications. Key Book Benefits Delivers practical guidance on how to develop Windows services using Visual Basic 2008 Covers integration of services with other Microsoft platforms including BizTalk, IIS, and SQL Server Features extensive code snippets and sample applications Visit the catalog page for Programming Windows® Services with Microsoft® Visual Basic® 2008Visit the errata page for Programming Windows® Services with Microsoft® Visual Basic® 2008Visit the supplemental content page for Programming Windows® Services with Microsoft® Visual Basic® 2008.